Effects of the Hungarian Privatizations on the Structure of the Hungarian Industry. - Bodo, Peter (1999)
Keywords: dept.eco; faculty_collection; sabbatical_report

"Banking It Before the Bar" - Crakes, Gary (1997)
Keywords: dept.eco; faculty_collection; sabbatical_report

Sino-American Relations and the Dependence Theory. - Hsu, David (1994)
Keywords: dept.eco; faculty_collection; sabbatical_report

Combining Ranked Mean Value Forecasts. - Mostaghimi, Mehdi (1993)
Keywords: dept.eco; faculty_collection; sabbatical_report

Management Science. - Hsiao, James (1990)
Keywords: dept.eco; faculty_collection

The Quality Imperative. - Clark, Jere (1989)
Keywords: dept.eco; faculty_collection; sabbatical_report

Thinker, Sailor, Brother, Spy - Maher, John (Maher & Maher, 1994)
Keywords: dept.eco; faculty_collection

Strategy Toward Congruence of Output and Employment Growth in a Labor Surplus Economy: A Case Study of Taiwan - HSu, Dave Y. C. (Taiwan Institute of Economic Research, 1984)
Keywords: 1945-; Economic conditions; Taiwan; dept.eco; faculty_collection

Management Science - Hsiao, J. C.; Cleaver, David S. (Houghton Mifflin, 1982)
Keywords: Management science; dept.eco; faculty_collection

A Linear Programming Approach to Financial Planning for Savings Banks - Terrell, Charles L.; Hsiao, James C. (Savings Bank, 1975)
Keywords: Linear programming; dept.eco; faculty_collection

Economics in the Curriculum - Calderwood, James D.; Lawrence, John D.; Maher, John Edward (Wiley, 1970)
National Task Force on Economic Education (U.S.). Economic education in the schools.
Keywords: Economics; Study and teaching (Secondary); United States; dept.eco; faculty_collection

The Impact of Imports on a Regional Economy: A Case Study of Greater Hartford, Connecticut - Bender, Mark Gregory (University Microfilms, 1967)
Keywords: Commerce; Commercial statistics; Import quotas; Foreign trade regulation; Commerce; Commercial policy; Hartford (Conn.); dept.eco; faculty_collection

Economic Specification of Cost Estimates in Dental Programs - Doherty, N.J.G.; Crakes, G.M. (Journal of Dental Research, 1985)
This paper compares two approaches to the estimation of costs in dental care programs: a conventional approach and an approach based on theoretical expectations. The conventional approach typically uses a linear extrapolation of an average figure - e.g., cost per visit - over various program sizes and thus predicts constant costs. Constant costs are, however, theoretically implausible, and it should be anticipated that their use in program planning or analysis would generate biased estimates. This hypothesis is examined using annual costs and visits from a group of uniform clinics over a five-year period. Results show that costs calculated by the conventional method are underestimated at low volumes and increasingly overestimated at higher volumes. The findings, which illustrate how inefficiency can inadvertently be incorporated into program design, have implications for cost-effectiveness of dental care delivery in the public sector. © 1985, SAGE Publications. All rights reserved.
Keywords: Child; Cost-Benefit Analysis; Delivery of Health Care; Dental Care; Dental Clinics; Dental Health Services; Human; cost; dental health; dept.eco; economic aspect; geographic distribution; health program; human; normal human; organization and management; prevention; short survey; therapy; tooth; united states

What are you thinking? - Groninger, S. (Psychological Perspectives, 1996)
Keywords: dept.eco

Non-linear characteristics of the sterling/european currency unit exchange rate: 1984–1992 - Chappell, D.; Eldridge, R.M. (International Journal of Phytoremediation, 1997)
The behaviour of the Sterling/European Currency Unit (ECU) exchange rate is examined both during the time before Britain joined the European exchange rate mechanism (ERM) and during the time of Britain's membership. During the latter period, a GARCH (1, 1) model fits the data well but during the pre-ERM period there is evidence of significant non-linear - possibly chaotic - structure in the GARCH residuals. Analysis of the dominant Lyapunov exponents and correlation dimension for the pre-ERM period suggests that the data generation process may be chaotic and this is reinforced by the highly significant BDS statistics obtained for this sample period. © 1997, Taylor & Francis Group, LLC.
Keywords: Non-linearity; Sterlingecu exchange rate; dept.eco; dept.fin

The Art of Soaring* - Clark, Jere W.; Clark, Juanita Stone (The Journal of Creative Behavior, 1979)
Keywords: dept.eco

General systems perspectives - Clark, Jere W (Journal of Creative Behavior, 1977)
Keywords: dept.eco

On facing the crisis of intellectual poverty* - Clark, Jere W. (The Journal of Creative Behavior, 1969)
Keywords: dept.eco

The critical shift point policy for housing abandonment - Levinson, Michael S; Hsiao, J C (Atlantic Economic Journal, 1975)
Keywords: dept.eco; dept.fin

An Economic Interpretation of the Transportation Problem - Hsiao, J.C. (American Journal of Agricultural Economics, 1971)
Keywords: dept.eco; dept.fin

The greek hyperinflation and stabilization of 1943-1946: A comment on makinen - Karatzas, George (The Journal of Economic History, 1988)
Keywords: dept.eco

Combining ranked mean value forecasts - Mostaghimi, Mehdi (European Journal of Operational Research, 1996)
A methodology is developed for combining mean value forecasts using not only all the important statistics related to the past performance and the dependence of the individual forecasts, but also a rank ordering of the individual forecasts representing the belief of a decision maker about the future performance of the forecasts. The maximum likelihood combination of the forecasts turns out to be a weighted linear combination of the individual forecasts, where the weights are a function of the rank order of the forecasts, correlation coefficients between the forecasts, and relative entropy information measures between the individual forecasts and the actual values. These weights are assessed once in the most general case and once in a special case where the forecasts are normally distributed. The sensitivity of the weights is also investigated. A sample application of this method for predicting U.S. hog prices is also presented.
Keywords: Combining forecasts; Combining ranked forecasts; Costs; Decision making; Estimation; Forecasting; Industrial applications; Marketing; Mathematical models; Maximum likelihood estimation; Maximum principle; Operations research; Performance; Rank ordering; Relative entropy; Statistical methods; dept.eco

Probability forecast of downturn in U.S. economy using classical statistical decision theory - Mostaghimi, Mehdi; Rezayat, Fahimeh (Empirical Economics, 1996)
This paper presents a methodology for producing a probability forecast of a turning point in U.S. economy using Composite Leading Indicators. This methodology is based on classical statistical decision theory and uses information-theoretic measurement to produce a probability. The methodology is flexible using as many historical data points as desired. This methodology is applied to producing probability forecasts of a downturn in U.S. economy in the 1970-1990 period. Four probability forecasts are produced using different amounts of information. The performance of these forecasts is evaluated using the actual downturn points and the scores measuring accuracy, calibration, and resolution. An indirect comparison of these forecasts with Diebold and Rudebusch's sequential probability recursion is also presented. It is shown that the performances of our best two models are statistically different from the performance of the three-consecutive-month decline model and are the same as the one for the best probit model. The probit model, however, is more conservative in its predictions than our two models.
Keywords: Business Cycle; Composite Leading Indicators; Information Theory; Likelihood Ratio; Probability Forecast Evaluation; Probability Forecast of a Turning Point; USA; composite leading indicator; dept.eco; economic performance; methodological evaluation; probability forecast

The use of least median of squares in the estimation of land value equations - Thorson, James A (Journal of Real Estate Finance and Economics, 1994)
Ordinary least squares (OLS) regression is relatively sensitive to the presence of outliers in a data set. In this paper, a robust estimation method, least median of squares (LMS) is used to identify outliers in land value data. Once the outliers are identified, are the land value equations re-estimated. The results show that a few observations can have a significant effect on the estimated coefficients. Finally, the observations which were identified as outliers were examined in more detail. One cause of outliers is an omitted variable. In this case, a large fraction of the outliers were found to be observations with high development potential.
Keywords: dept.eco; least median of squares; outliers

Zoning policy changes and the urban fringe land market - Thorson, James A (Real Estate Economics, 1994)
This paper examines the effect of a zoning change on the land market in McHenry County, Illinois. One question addressed is whether zoning `'follows the market.” It is found that, for agricultural land, zoning does tend to follow the market. In addition, the effect of land prices on land use is examined. The results here, however, are mixed. In the initial years after the zoning change, a high relative price of residential land increases the probability that a parcel will be zoned residential. However, several years later, a high relative price of residential land decreases the probability that a parcel is zoned residential. This result suggests that it may take some time for a zoning change to have a significant impact on the local land market.
Keywords: dept.eco

Obstacles to trade liberalization and economic cooperation among west African states - Gebremariam, Yilma (Journal of International Development, 1993)
Does the formation of a customs union reduce and eventually eliminate tariffs among member countries to provide mechanisms or regional institutions for social, economic and political development? The literature examined suggests that, although many problems of trade liberalization continue to occur, greater benefits could be obtained by reducing tariffs on a non‐discriminatory basis, or by removing protection from domestic enterprises altogether, and by importing domestic requirements of the products of displaced industries from outside at world market prices. The literature also provides a valid case for protecting certain activities in ECOWAS — particularly trade and industrial enterprises — either for the purpose of increasing income or the rate of economic growth, or in order to achieve certain non‐economic objectives. The implications of economic integration in these terms can best be examined within a broader theoretical framework of developmental theory of trade liberalization. Copyright © 1993 John Wiley & Sons, Ltd
Keywords: Africa, (West); ECOWAS; customs union; dept.eco; developing country; economic cooperation; free trade area; international trade; regional cooperation; tariff reduction; trade liberalisation

Labor shortage and unutilized labor reserve in Taiwan - Hsu, Dave Y C; Hwang, Jen Te (Journal of Contemporary Asia, 1992)
By 1965, Taiwan has changed from a labor surplus economy into a labor shortage economy. This article examines how rising demand for labor due lo rapid economic growth in Taiwan has been met since 1965. This article attempts to answer 1) Where did the labor supply come from? 2) Has all of the potential labor supply been tapped and exhausted? 3) Is it possible for labor shortage and unutilized labor reserve to occur simultaneously? The authors hope that this study will lead to a better understanding of the limitation of the free market mechanism and help identify the proper public policies to enhance labor utilization.
Keywords: dept.eco

Rates of return on art objects, the fisher hypothesis, and inflationary expectations - Matsumoto, Keishiro; Andoh, Samuel K; Hoban, James P (The Financial Review, 1994)
After surveying the evolution of the major methodologies in inflation hedging, this study presents a unique methodology that uses principal component factor analysis to separate the effects of variability in the real rate of return from the nominal rate of return. This approach allows the effects of both anticipated and unanticipated inflation on rates of return to be estimated more precisely. This study finds that art objects perform well in terms of average real rates of return and that the market, though not perfect, integrates anticipated inflation into the rates of return. However, unanticipated inflation is very often negatively related to the rates of return. Copyright © 1994, Wiley Blackwell. All rights reserved
Keywords: dept.eco; dept.fin

Controlled chain reaction as a regulatory technique - Bodo, Peter (International Advances in Economic Research, 1996)
This paper discusses a regulatory technique that consists of the use of a controlled chain reaction to influence social and economic processes. It claims that this method was employed by Hungarian control agencies to further centralize the farm sector in the 1970s. Section I of the paper presents three versions of this technique. Section II shows how the institutional structure of Hungarian agriculture made the application of this technique possible. (JEL P21).
Keywords: dept.eco; dept.fin

The effect of zoning on housing construction - Thorson, James A (Journal of Housing Economics, 1997)
This paper examines whether a more restrictive zoning ordinance actually reduces construction of new housing. This may seem at first to be a trivial issue, since why else would a zoning board make the ordinance more restrictive. However, it is possible for landowners to circumvent the zoning law. For example, they can subdivide their land before the zoning change occurs. In addition, they can bargain with the local zoning officials and offer side payments, also known as exactions, for the right to develop their land. This paper examines a famous case of agricultural downzoning in McHenry County, Illinois. It finds that although the number of building permits issued did not fall immediately, in the long run the number of permits issued by the county was significantly reduced. This suggests that developers were able to anticipate the zoning change and subdivide their land before it occurred. (C) 1997 Academic Press.
Keywords: dept.eco; dept.fin

An examination of the monopoly zoning hypothesis - Thorson, J.A. (Land Economics, 1996)
There have been several studies that have investigated the effect of zoning on housing prices. One hypothesis is that the restrictiveness of zoning laws will vary with the monopoly power of a town. The degree of monopoly power varies with the number of towns in the urban area. Urban areas with few zoning jurisdictions are likely to have higher housing prices than more fragmented urban areas. Previous research on this topic has shown mixed results. The results in this article suggest that towns with more monopoly power do tend to have significantly higher housing prices than more fragmented urban areas.
Keywords: dept.eco; dept.fin